Graph the circle with center at (-1, 2) and diameter 12. Label the center and at least four points on the circ?
-
1. Graph the circle with center at (-1, 2) and diameter 12. Label the center and at least four points on the circle. Write the equation of the circle. 2. Graph the circle with center at (3, -2), which also passes through the point (0, 2). Label the center and at least four points on the circle. Write the equation of the circle. 3.Graph the circle with center at (-1, -2), which also passes through the point (0, 2). Label the center and at least four points on the circle. Write the equation of the circle. 4. Challenge: Graph the equation with a diameter that has endpoints at (-3, 4) and (5, -2). Label the center and at least four points on the circle. Write the equation of the circle. 5. Challenge: Graph the equation with a diameter that has endpoints at (-2, -2) and (4, 2). Label the center and at least four points on the circle. Write the equation of the circle.
-
Answer:
5. Graph the equation with a diameter with endpoints (-2, -2) and (4, 2). First off, since (-2, -2) and (4, 2) comprise the diameter of the circle, calculate the distance using the distance formula. d = sqrt ( (x2 - x1)^2 + (y2 - y1)^2 ). Let (x1, y1) = (-2, -2) and (x2, y2) = (4, 2). d = sqrt( (4 - (-2))^2 + (2 - (-2))^2 ) d = sqrt( (4 + 2)^2 + (2 + 2)^2 ) d = sqrt( 6^2 + 4^2 ) d = sqrt( 36 + 16) d = sqrt(52) d = sqrt(4 * 13) d = 2sqrt(13) So the distance (and therefore diameter) is equal to d = sqrt(52). Next, we need to find the center of the circle. The center is simply the average of the x-coordinates, and the average of the y-coordinates. Let's call (h, k) the coordinates of the circle. h = (x1 + x2)/2 = (-2 + 4)/2 = 2/2 = 1 k = (y1 + y2)/2 = (-2 + 2)/2 = 0/2 = 0 So the center is located at (1, 0). The formula of a circle is (x - h)^2 + (y - k)^2 = r^2 So we want the radius r. Since the diameter is 2sqrt(13), and the radius is half the diameter, it follows that r = (1/2) of diamater r = (1/2) (2sqrt(13)) r = sqrt(13) Making the formula (x - h)^2 + (y - k)^2 = r^2 Given that r = sqrt(13), (h, k) = (1, 0), we get (x - 1)^2 + (y - 0)^2 = [sqrt(13)]^2 (x - 1)^2 + y^2 = 13
bumblebe... at Yahoo! Answers Visit the source
Related Q & A:
- Is there any way to connect USB in computers to Playstation 1/2/3's controller?Best solution by Yahoo! Answers
- With which 2 castaways on the island were Gilligan's 2 most significant relationships? Label or describe each?Best solution by Yahoo! Answers
- Should I upgrade to OS 3.1.2?Best solution by answers.yahoo.com
- Can I Jailbreak my iPhone on 3.1.2?Best solution by ChaCha
- How do you multiple 1 2/3 by 3 1/8?Best solution by themathpage.com
Just Added Q & A:
- How many active mobile subscribers are there in China?Best solution by Quora
- How to find the right vacation?Best solution by bookit.com
- How To Make Your Own Primer?Best solution by thekrazycouponlady.com
- How do you get the domain & range?Best solution by ChaCha
- How do you open pop up blockers?Best solution by Yahoo! Answers
For every problem there is a solution! Proved by Solucija.
-
Got an issue and looking for advice?
-
Ask Solucija to search every corner of the Web for help.
-
Get workable solutions and helpful tips in a moment.
Just ask Solucija about an issue you face and immediately get a list of ready solutions, answers and tips from other Internet users. We always provide the most suitable and complete answer to your question at the top, along with a few good alternatives below.